Phenotypic assessment of rice landraces for genetic variability and diversity studies under heat stress - Lavanya, Kakarla; K, Suman; Fiyaz, Abdul R; Chiranjeevi, M; Surender, R; Satya, A Krishna; Sudhakar, P; Subba Rao, Lella V (ORYZA-An International Journal of Rice, 2022)
The present investigation was carried out to estimate the genotypic and phenotypic variability, heritability, genetic advance and divergence based on heat stress and yield associated traits using 48 landraces of rice grown during rabi 2016 and 2017 at ICAR-Indian Institute of Rice Research farm, Hyderabad. ANOVA revealed the existence of significant differences for all the traits under study. Phenotypic coefficient of variation (PCV) was found slightly elevated than the genotypic coefficient of variation (GCV). All the characters under study except time to maturity exhibited high heritability coupled with high genetic advance as a per cent of mean, which revealed the predominance of additive gene action in controlling these traits. Cluster analysis grouped the 48 landraces into ten distinct clusters. Cluster I consisted of one landrace, while cluster II and III had 9 landraces each. Clusters IV, V, VI, VII, VIII, IX and X had 6, 2, 3, 3, 1, 6 and 8 landraces respectively. Cluster I included one landrace Byama Jhupi which was superior for the trait number of grains per panicle.Â Highest single plant yield (Mugei), fertility percentage (Neta) and time of heading (Neta) were recorded by entries of cluster II and highest panicle number per plant was recorded by landrace (Chiiti Mutyalu) of cluster IX. The genotypes of cluster II, VIII and IX showed high spikelet fertility percentage. Hence the genetic resources of these clusters can be utilized in the breeding programmes for development of heat tolerant varieties. The study helped to understand the extent of genetic diversity among the genetic resources which serve as a treasure of highly useful traits which can be exploited in developing high yielding and stress tolerant varieties.